Customer Satisfaction on Yamaha Motorcycles: A Study of Product Differentiation and Brand Reputation - Dikdik Harjadi; Iqbal Arraniri; Diki Sagita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims at analyzing the effect of product differentiation and brand reputation on customer satisfaction of Yamaha motorcycle products. To collect data, questionnaires were distributed to 100 respondents selected through accidental sampling method. Meanwhile, descriptive and verification testing methods were used to analyze the collected data. Besides, multiple linear regression was also used to construct the variables, namely product differentiation (X1), brand reputation (X2), and customer satisfaction (Y). As results, this study found that product differentiation and brand reputation have a significant effect on costumer satisfaction